Calculation of Human Development Indices in Turkish Provinces. A Comprehensive Panel Dataset for the 2009- 2018 Period - Nadide Yiğiteli; Devran Şanlı (Journal of Economy Culture and Society)
The human development index was designed in 1990 to evaluate countries’ development levels within the framework of UNDP. Followingthis, a series of indices were developed to analyze the different dimensions of human development. While these indices make intercountry comparisons, they do not allow evaluation at a local level. However, determining human development at the local level has great importance. For this purpose, using UNDP methodology, four different indices were calculated at the province level covering the period between 2009 and 2018. In this respect, a comprehensive data set is presented to the literature. The results show that, although provinces have progressed in all aspects of human development, they have not yet been able to reach a very high human development category. The primary factor restraining human development levels is found to be low degrees of education in the provinces. Although regional and gender inequalities both in education and in income distribution have decreased, they are nonetheless still quite high. The most developed provinces by the HDI index are Ankara, Istanbul, and Kocaeli, whereas the lowest provinces are Van, Şanlıurfa, and Ağrı. By the inequality-adjusted HDI no province has as yet reached a very high human development level. While the minimum loss due to inequality was seen in Muğlathe province, the highest loss is in Hakkari.